Organized Crime and Preventive Justice - Sorell, Tom (Ethical theory and moral practice, 2018)
By comparison with the prevention of terrorism, the prevention of acts of organized crime might be thought easier to conceptualize precisely and less controversial to legislate against and police. This impression is correct up to a point, because it is possible to arrive at some general characteristics of organized crime, and because legislation against it is not obviously bedeviled by the risk of violating civil or political rights, as in the case of terrorism. But there is a significant residue of legal, moral and political difficulty: legislation against organized crime is hard to make effective; the harm of organized crime is not uniform, and so some preventive legislation seems too sweeping and potentially unjust. More fundamentally, the scale and rewards of organized crime are often dependent on mass public participation in markets for proscribed goods, which may point to a hidden public consensus in favour of some of what is criminalized. For all of these reasons, I argue that existing preventive policing and legislation against organized crime may be harder to justify than their counterparts in counter-terrorism, at least in the UK.